2012
DOI: 10.1111/j.1464-5491.2011.03541.x
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus in Europe: prevalence, current screening practice and barriers to screening. A review

Abstract: Background Gestational diabetes mellitus is a potentially serious condition that affects many pregnancies and its prevalence is increasing. Evidence suggests early detection and treatment improves outcomes, but this is hampered by continued disagreement and inconsistency regarding many aspects of its diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
230
7
14

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(269 citation statements)
references
References 56 publications
18
230
7
14
Order By: Relevance
“…A recent review also shows that screening and management of GDM is very variable across Europe, partly due to the ongoing controversy and inadequate clinician awareness of GDM [23]. A recent survey performed in the northern part of Belgium highlights that policies are often also inconsistent even within one region [24].…”
Section: An Ebcog Initiative To Develop a Proposal For The Use Of Unimentioning
confidence: 99%
“…A recent review also shows that screening and management of GDM is very variable across Europe, partly due to the ongoing controversy and inadequate clinician awareness of GDM [23]. A recent survey performed in the northern part of Belgium highlights that policies are often also inconsistent even within one region [24].…”
Section: An Ebcog Initiative To Develop a Proposal For The Use Of Unimentioning
confidence: 99%
“…Also, offspring of mothers with GDM have increased risk of obesity and diabetes later in life [6,7]. Globally, the prevalence of GDM has increased within the last 20 years [8,9]. The first study of GDM performed in Greenland reported a very low prevalence of GDM among women from Nuuk who gave birth in 2008 [10].…”
Section: Introductionmentioning
confidence: 99%
“…The same can be done at undergraduate and postgraduate levels by curriculum planners. Similar campaigns are underway in Europe as well [9].…”
mentioning
confidence: 95%